53.5k views
0 votes
Operations with Radical ExpressionsThis is a new topic that I’ve never done before so I’m not sure where to start

Operations with Radical ExpressionsThis is a new topic that I’ve never done before-example-1
User Annalise
by
5.1k points

1 Answer

6 votes

We need to simplify the expression:


-2\sqrt[]{20}-2\sqrt[]{24}-2\sqrt[]{24}

We can start by grouping the second and third terms since they have the same factor:


-2\sqrt[]{24}-2\sqrt[]{24}=(-2-2)\sqrt[]{24}=-4\sqrt[]{24}

Then, we need to simplify:


-2\sqrt[]{20}-4\sqrt[]{24}

Now, we can factor the number inside each square root:


\begin{gathered} 20=2\cdot2\cdot5=2^2\cdot5 \\ \\ 24=2\cdot2\cdot2\cdot3=2^2\cdot6 \end{gathered}

And we can use the following properties:


\begin{gathered} \sqrt[]{a.b}=\sqrt[]{a}\cdot\sqrt[]{b} \\ \\ \sqrt[]{n^(2)}=n,\text{ for }n\ge0 \end{gathered}

Then, we obtain:


\begin{gathered} \sqrt[]{20}=\sqrt[]{2^2\cdot5}=\sqrt[]{2^(2)}\cdot\sqrt[]{5}=2\sqrt[]{5} \\ \\ \sqrt[]{24}=\sqrt[]{2^2\cdot6}=\sqrt[]{2^(2)}\cdot\sqrt[]{6}=2\sqrt[]{6} \end{gathered}

Using the above results in the expression, we find:


-2\sqrt[]{20}-4\sqrt[]{24}=-2\cdot2\sqrt[]{5}-4\cdot2\sqrt[]{6}=-4\sqrt[]{5}-4\cdot2\sqrt[]{6}

Since both terms have the factor -4, we can group it to obtain:


-4(\sqrt[]{5}+2\sqrt[]{6})

Therefore, a way to simplify the given expression is by writing it as:


-4(\sqrt[]{5}+2\sqrt[]{6})

User Thomas Aylott
by
5.2k points